Rotationally resolved zero-kinetic-energy photoelectron spectrum of nitrogen. - Merkt, F; Softley, T (1992)
Rotationally resolved zero-kinetic-energy (ZEKE) photoelectron spectra of the X g+2(v+=0,1) X g+1(v=0) bands of nitrogen have been recorded. The spectra show unexpected rotational-line intensities. The intensity distortions are explained by channel interactions. The strong S and U branches [(N+-J)=+2 and +4, respectively] of the (1-0) band borrow intensity from a nearly degenerate Rydberg state, converging to an electronic excited state of the ion, by a complex resonance mechanism. Field-induced rotational autoionization is shown to enhance the O branch and M branch [(N+-J)=-2 and -4] intensity of the (0-0) band. Recording ZEKE spectra with extraction fields of 10100 V/cm appears to be an attractive and powerful way of obtaining spectroscopic information on Rydberg states with simultaneously high principal quantum number n and high total-angular-momentum quantum number J. © 1992 The American Physical Society.